Expression Patterns, Genomic Conservation and Input Into Developmental Regulation of the GGDEF/EAL/HD-GYP Domain Proteins in Streptomyces - Al-Bassam, Mahmoud M.; Haist, Julian; Neumann, Sara Alina; Lindenberg, Sandra; Tschowri, Natalia (Frontiers in Microbiology, 2018)
To proliferate, antibiotic-producing Streptomyces undergo a complex developmental transition from vegetative growth to the production of aerial hyphae and spores. This morphological switch is controlled by the signaling molecule cyclic bis-(3´,5´)-cyclic di-guanosine-mono-phosphate (c-di-GMP) that binds to the master developmental regulator, BldD, leading to repression of key sporulation genes during vegetative growth. However, a systematical analysis of all the GGDEF/EAL/HD-GYP proteins that control c-di-GMP levels in Streptomyces is still lacking. Here, we have Flag-tagged all 10 c-di-GMP turnover proteins in Streptomyces venezuelae, and characterized their expression patterns throughout the life cycle, revealing that the diguanylate cyclase (DGC) CdgB and the phosphodiesterase (PDE) RmdB are the most abundant GGDEF/EAL proteins. Moreover, we have deleted all the c-di-GMP genes individually and analyzed morphogenesis of the mutants in macrocolonies. We show that the composite GGDEF-EAL protein CdgC is an active DGC in vivo and that deletion of the DGCs cdgB and cdgC enhance sporulation whereas deletion of the PDEs rmdA and rmdB delay development in S. venezuelae. By comparing the pan genome of 93 fully sequenced Streptomyces species we show that the DGCs CdgA, CdgB, and CdgC and the PDE RmdB represent the most conserved c-di-GMP-proteins in the genus Streptomyces.